Contribuições do programa de residência pedagógica na formação docente dos licenciandos em matemática - CORDEIRO, Ananda Ferreira (2022)
The present work consists in the exposition of the experiences lived by the undergraduates of the Degree in Mathematics of the Federal University of Pará -University campus of Abaetetuba, called residents. The research was based on experience reports produced by residents each semester. Despite the pandemic context, the program provided residents with eighteen months of teaching insertion in high school classes at a school in the state network of Pará, located in the municipality of Abaetetuba, with the production of teaching materials, conducting classes, pedagogical training, meetings of planning and elaboration of works for scientific events, under the active guidance of the preceptor professor. Based on the reports, the study aims to show the contributions of the Pedagogical Residency Program (PRP) in the training of future mathematics teachers, promoting reflection on being a teacher in the perspective of associating theory with practice. It concludes by showing the activities developed during the program, which made it possible for residents to know and experience the day-to-day life of the basic education school, which is so important in the process of training future teachers.